A Bibliometric Analysis Of Green Accounting Research - Rizka, Hifzhii Nur; Hastina, Hastina; Pramono, Sigid Eko (JAS (Jurnal Akuntansi Syariah), 2024)
The primary goal of green accounting is to address social issues impacting global sustainable development and to influence corporate actions towards social and environmental concerns. This research aims to map the concept of green accounting and describe its impact on science. This research is a literature review using bibliometrics. Bibliometrics helps map research related to developing green accounting research trends published by leading journals from 1992 to 2023, which have been indexed by Scopus as many as 233 articles, using VosViewer software. The analysis is focused on keyword trends, authors, and institutions. The results show that the number of articles discussing the theme of green accounting has been increasing yearly, which aligns with the development of economics and the environment. The most popular keywords are sustainable development, environmental management, and environmental economics. The most published writer is Markandya. Meanwhile, the most popular organization is Fondazione Eni Enrico Mattei (FEEM). This study provides valuable insights for researchers focusing on green accounting. Therefore, this theme has the potential to be further developed in the future.